Evaluation and Implication of Case Volume Variation in Level 1 and 2 Trauma Centers - Patrick L. Johnson, MD, MPH; Bryant W. Oliphant, MD, MBA, MSc; Jonathan E. Williams, MD; Cody L. Mullens, MD, MPH; Raymond A. Jean, MD; Anne H. Cain-Nielsen, MS; John W. Scott, MD, MPH; Mark R. Hemmila, MD (Annals of Surgery Open, 2025)
Objective:. To evaluate variation in case volume and procedural volume across level 1 and 2 U.S. trauma centers. Background:. When trauma center distribution does not fit regional needs, the longstanding volume-outcomes relationship in trauma care is at risk. Case volume variability has important implications for trauma center distribution, patient outcomes, and clinical skills maintenance. Methods:. We placed trauma centers into quintiles based on average annual patient volume meeting American College of Surgery Trauma Quality Improvement Program (ACS TQIP) inclusion criteria from 2017 to 2021. Patient characteristics and procedures performed were evaluated across case volume and trauma center verification levels. We evaluated the relationship between procedural volume and case volume by examining the number of interventions performed as a proportion of patients with a potential indication. Results:. We identified 1,902,005 patients among 228 level 1 and 288 level 2 trauma centers. A fourfold difference in ACS TQIP qualifying patient volume was present between the highest and lowest quintile level 1 and 2 trauma centers (1888 ± 481 vs 484 ± 109, 966 ± 223 vs 224 ± 70). The lowest quintile centers performed very low volumes of essential trauma procedures including hemorrhage control (22 per year) and pelvic fracture operations (10 per year). Low-volume trauma centers performed proportionally fewer procedures, including hemorrhage control procedures for patients presenting with tachycardia and hypotension (25.9 vs 31.8%, P < 0.001). Conclusions:. Trauma center case volume varies widely, with 1-in-5 level 1 trauma centers averaging <2 hemorrhage control procedures per month. Furthermore, low-volume centers perform proportionally fewer procedures suggesting unexplained variation in practice patterns.